Communicable Diseases Intelligence volume 5 issue 7 - 10 April 1981 - whole issue - No author listed, (Communicable Diseases Intelligence, 1981)
Whole-issue pdf, comprising: Virus Reporting Scheme Article Human salmonellosis surveillance Salmonellosis and marijuana - U.S.A. Echovirus type 9 outbreak in a residential home for children [Victoria] Publication Notice "The Culicidae of the Australasian Region" by The Commonwealth Institute of Health, Sydney Notice to Readers National Venereology Council for Australia [recently inaugurated professional body] Corrigendum "In CDI 81/3 page 5, it was stated that mecillinam (Selexid) was marketed by Boehringer Ingelheim Pty Ltd. We have since been informed that the drug was imported for a veterinary trial, and is no longer available from the company." [end] "In CDI 81/6 page 5, it was stated that "Trypticase soy broth or Trypticase soy broth with 6.5% NaC1 were used as Staphylococcal selective media". This sentence should have read "The media used were Tryticase soy broth, or Trypticase soy broth with 6.5% NaC1 to provide a selective environment for Staphylococcal"." [end] Human Salmonellosis Cases Period October - December 1980 Australia - Communicable Diseases Intelligence Reporting Period - 19/03/1981 to 01/04/1981 Bulletin Number 81/7